Halide Perovskites: A New Era of Solution‐Processed Electronics. Issue 23 (3rd May 2021) - Younis, Adnan; Lin, Chun‐Ho; Guan, Xinwei; Shahrokhi, Shamim; Huang, Chien‐Yu; Wang, Yutao; He, Tengyue; Singh, Simrjit; Hu, Long; Retamal, Jose Ramon Duran; He, Jr‐Hau; Wu, Tom
Abstract: Organic–inorganic mixed halide perovskites have emerged as an excellent class of materials with a unique combination of optoelectronic properties, suitable for a plethora of applications ranging from solar cells to light‐emitting diodes and photoelectrochemical devices. Recent works have showcased hybrid perovskites for electronic applications through improvements in materials design, processing, and device stability. Herein, a comprehensive up‐to‐date review is presented on hybrid perovskite electronics with a focus on transistors and memories. These applications are supported by the fundamental material properties of hybrid perovskite semiconductors such as tunable bandgap, ambipolar charge transport, reasonable mobility, defect characteristics, and solution processability, which are highlighted first. Then, recent progresses on perovskite‐based transistors are reviewed, covering aspects of fabrication process, patterning techniques, contact engineering, 2D versus 3D material selection, and device performance. Furthermore, applications of perovskites in nonvolatile memories and artificial synaptic devices are presented. The ambient instability of hybrid perovskites and the strategies to tackle this bottleneck are also discussed. Finally, an outlook and opportunities to develop perovskite‐based electronics as a competitive and feasible technology are highlighted. Abstract : Organic–inorganic halide perovskites show high promise for electronic devices owing to exceptional electrical, optical, and structural properties. The latest breakthroughs in structural, interface, defect engineering, and pattering techniques as applied to halide perovskite transistors, memories and to improve stability issues in perovskites are reviewed. Lastly, the existing challenges and outline for future research directions are provided.